Le Recueil Lauvergne (1680) de Claude Barbin. Écriture en groupe ou coup d’éditeur ? - Stephanie Bung (Les Dossiers du GRIHL)
Published in 1680, the Recueil de poésies par Madame de Lauvergne, dédié à Madame la Marquise de Neuville, also known as Recueil Lauvergne, is a heterogeneous collection of poems whose construction informs us about the social issues that shape many of the editorial processes of the time. Collective writing can be considered as being essential to those practices, especially within the realm of gallant poetry. The editor Claude Barbin is fully aware of this since he equips his book with a dedication that seems to refer to a privileged milieu, to some kind of “salon-writing” (Joan DeJean) or even to a precise patronage relationship. This article aims at enquiring into this scenography of the literary collective without however denouncing it as pure fiction. For if there is a "group effect", it is because the exclusivity of such groups is not invented, but drawn against the light in the Lauvergne Collection.